Chronic-graft-versus-host-disease-related polymyositis: a 17-months-old child with a rare and late complication of haematopoietic stem cell transplantation. - Matteo Chinello; Rita Balter; Massimiliano De Bortoli; Virginia Vitale; Ada Zaccaron; Elisa Bonetti; Paola Tonin; Gaetano Vattemi; Valeria Guglielmi; Simone Cesaro (Mediterranean Journal of Hematology and Infectious Diseases)
Background: Chronic graft versus host disease (cGVHD) occurs in 20-30% of paediatric patients receiving haemopoietic stem cell transplantation (HSCT). Neuromuscular disorders such as polymyositis are considered a rare and distinctive but non-diagnostic manifestation of cGVHD and, in absence of other characteristic signs and symptoms, biopsy is highly recommended to exclude other causes.